2013 22nd International Conference on Computer Communication and Networks (ICCCN) 2013
DOI: 10.1109/icccn.2013.6614138
|View full text |Cite
|
Sign up to set email alerts
|

Fast Near-Optimal Algorithm for Delivering Multiple Live Video Channels in CDNs

Abstract: Abstract-Content Delivery Networks (CDNs) are confronted with a sharp increase in traffic related to live video (channel) streaming. Previous theoretical models that deal with streaming capacity problems do not capture the emerging reality faced by today's CDNs. In particular, a modern CDN has to deliver a large set of independent non-divisible data streams, which need to be either delivered in whole, or not delivered at all. This constraint is not addressed in previous works.In this paper we identify a new, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The first set of work related to discretized streaming has been published in a conference paper [23]. This paper significantly extend our previous work by considering a more general application scenario and proposing fast near-optimum algorithm for it.…”
Section: Introductionmentioning
confidence: 87%
“…The first set of work related to discretized streaming has been published in a conference paper [23]. This paper significantly extend our previous work by considering a more general application scenario and proposing fast near-optimum algorithm for it.…”
Section: Introductionmentioning
confidence: 87%
“…These works cannot be extended to multi-source multi-channel live streaming due to the shared resources such as link capacity and server upload bandwidth. Though some works have been done on multi-channel P2P live streaming [8]- [12], they consider different objective functions, such as maximizing bandwidth to support more users or minimizing the load of servers through collaboration of users. Few have addressed how to optimize the overall streaming delay, which is an important metric for user experience in live streaming.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have shown that coupling layered video with adaptive streaming [34] can generate important bandwidth savings but such solution is still in its infancy today. Finally, a discretized streaming model for live rate-adaptive video streaming has been proposed in [35]. The goal is to maximize the utility of delivered streams.…”
Section: ) Overall Performancesmentioning
confidence: 99%